Socio-Technical Barriers to Drip Irrigation Adoption in Fodder Farming: An Ex-Post-Facto Study from Ghayathi, Abu Dhabi, UAE - Arshad, Imran; Ali, Ali Ahmed; Almansoori, Mubarak Ahmed Saleh; Philip, Phiji Jacob; Afzal, Wakeel; Khan, Zaheer Ahmed (PSM Biological Research, 2025)
This study explores the constraints and perceptions of fodder growers in Ghayathi, Abu Dhabi, regarding the adoption and maintenance of drip irrigation systems in an arid agricultural setting. Based on data from 150 farmers, the findings reveal high adoption rates driven by recognized benefits such as water savings (90%), increased yield (85%), and reduced labor (70%). However, technical challenges including emitter clogging (94.67%), pipeline leakages (79.33%), and rodent damage (71.33%) alongside limited education and modest landholdings, hinder effective system management. The study underscores the need for targeted extension services, accessible technical support, and affordable maintenance solutions to ensure the long-term sustainability of drip irrigation in fodder cultivation.